2022
DOI: 10.3390/su14074042
|View full text |Cite
|
Sign up to set email alerts
|

Education on Sustainable Development Goals: Geographical Perspectives for Gender Equality in Sustainable Cities and Communities

Abstract: Because of its interdisciplinary approach as a social science directly related to the natural sciences, geography is the academic discipline and school subject that equips students well with knowledge, skills, and values related to education on sustainable development goals. This study is part of the results of MyGEO, a project funded by the European Commission, and it is based on a collaborative mapping of streets named after women in a medium-sized city (Zaragoza, Spain), in connection with the international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this case, they value positively the incorporation of the SDGs in university geographic education, perhaps because they know their expectations better, but precisely because of this, they are also more critical than students when they value their actual presence. Among teachers, significantly different perceptions are observed depending on the area to which they belong, in keeping with the traditional division between social and environmental geographic researchers (De Miguel González and Sebastián-López, 2022) with different conceptions. Among students, those who are still active are more idealistic and score better than those who have already graduated, whose worse scores may reflect discouragement in the face of the poor situation of the labor market in which they find themselves or which they are trying to access (Colegio de Geógrafos, 2018).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this case, they value positively the incorporation of the SDGs in university geographic education, perhaps because they know their expectations better, but precisely because of this, they are also more critical than students when they value their actual presence. Among teachers, significantly different perceptions are observed depending on the area to which they belong, in keeping with the traditional division between social and environmental geographic researchers (De Miguel González and Sebastián-López, 2022) with different conceptions. Among students, those who are still active are more idealistic and score better than those who have already graduated, whose worse scores may reflect discouragement in the face of the poor situation of the labor market in which they find themselves or which they are trying to access (Colegio de Geógrafos, 2018).…”
Section: Discussionmentioning
confidence: 57%
“…Sustainability has usually been considered in the training of geography professionals within the theoretical framework of the “Decade of Education for Sustainable Development 2005–2014” promoted by the United Nations Education for Sustainable Development initiative or more recently with the SDGs (De Miguel González and Sebastián-López, 2022). However, different experts claim further steps (Grindsted and Nielsen, 2022) and have shown the importance in curricula of associating theoretical knowledge with the competences defended by UNESCO in 2014 (critical analysis, systemic reflection, collaborative decision-making and sense of responsibility toward present and future generations) and how it is related to skills such as critical thinking; ethical and intellectual commitment; relational and holistic thinking; sense of belonging to the community; argumentative skills; participatory skills; democratic commitment; and commitment to universal human rights (Murga-Menoyo, 2015).…”
Section: Literature Review: Sustainable Development Goals In Geograph...mentioning
confidence: 99%
“…Another factor that influences the number of students who enter package B is due to financial constraints that cannot be met if they enter formal education. For this reason, PKBM provides learning opportunities without burdening citizens to learn equality by providing free educational services (González & Sebastián-López, 2022).…”
Section: Raw Inputmentioning
confidence: 99%
“…Notably, its target 11.a aims to support positive economic, social, and environmental links between urban, peri-urban, and rural areas by strengthening national and regional development planning [7]. Furthermore, many studies have shown that SDG 4 and 5, quality education and gender equality, significantly contribute to achieving SDG 11, sustainable cities and communities [8][9][10][11][12]. However, there is a lack of research on the progress of SDG 11 focused on SDG 4 and 5 in Cambodia, particularly at the district level.…”
Section: Introductionmentioning
confidence: 99%